Intravenous dexmedetomidine v/s tramadol on post spinal anaesthesia shivering: A randomized, double blind and interventional study - Pooja Bharti; Yogesh Chand Modi; Subhita Marodia; Pushpendra Bairwa (Creative Pharma Assent, 2023)
Introduction: Regional anaesthesia is widely used and safe anaesthetic technique. It leads to Intra/ post-operative shivering. There are various methods available to control. Tramadol is one of the most widely used to control shivering, however it is also associated with nausea and vomiting. Objective: To compare the efficacy of dexmedetomidine and tramadol in the treatment of post‑spinal anesthesia (SA) shivering as well as to compare their side‑effect profile. Methodology: This hospital based, prospective, randomized, double blinded, Superiority type of interventional study included 60 patients undergoing elective spinal anesthesia aged 20-60 years, ASA grade I and II, weighing 40-80 kilograms. Subjects were randomly allocated into two groups, to receive either 0.5 mcg/kg Dexmedetomidine (Group D) or 05 mg/kg Tramadol (or grpup T). The grade of shivering was assessed as per wrench (Grade 0: no shivering, Grade 1: One or more of the following: piloerection, peripheral vasoconstriction, peripheral cyanosis, but without visible muscles activity, Grade 2: Visible muscle activity confined to one muscle group, Grade 3: Visible muscle activity in more than one muscle group and Grade 4: Gross muscle activity involving the whole body). Result: Shivering was eliminated in all the patients who received either dexmedetomidine or tramadol. Time for unset of shivering and grade of shivering is quite similar in both study groups. Time to cessation of shivering was significantly earlier with dexmedetomidine (174.3±12.5) as compare with tramadol (279.6±15.9). Nausea and vomiting is found significantly higher (P value = 0.024) with tramadol.